On the performance of profile extrusion dies - Pereira, S. P. (2012)
This work presents a study performed with an in-house 3D numerical modelling code, used to evaluate the sensitivity of extrusion dies, optimized with alternative strategies, to process parameters, such as machining inaccuracies, melt rheology and processing conditions.